Plasticity in the sensory systems of invertebrates - Elzbieta M. Pyza (Frontiers Research Topics, 2014)
The visual, olfactory, auditory and gustatory systems of invertebrates are often used as models to study the transduction, transmission and processing of information in nervous systems, and in recent years have also provided powerful models of neural plasticity. This Research Topic presents current views on plasticity and its mechanisms in invertebrate sensory systems at the cellular, molecular and network levels, approached from both physiological and morphological perspectives. Plasticity in sensory systems can be activity- dependent, or occur in response to changes in the environment, or to endogenous stimuli. Plastic changes have been reported in receptor neurons, but are also known in other cell types, including glial cells and sensory interneurons. Also reported are dynamic changes among neuronal circuits involved in transmitting sensory stimuli and in reorganizing of synaptic contacts within a particular sensory system. Plastic changes within sensory systems in invertebrates can also be reported during development, after injury and after short or long- term stimulation. All these changes occur against an historical backdrop which viewed invertebrate nervous systems as largely hard-wired, and lacking in susceptibility especially to activity-dependent changes. This Research Topic examines how far we have moved from this simple view of simple brains, to the realization that invertebrate sensory systems exhibit all the diversity of plastic changes seen in vertebrate brains, but among neurons in which such changes can be evaluated at single-cell level.